The Influence of Leadership, Rewards, and Supervision on Work Discipline at PT Herfinta Farm & Plantation - Sinaga, Soleh Huddin; Sebayang, Saimara A.M.; Robain, Wilchan (Utan Kayu Publishing, 2026)
This study aims to determine the positive and significant influence of leadership style, rewards, and supervision on work discipline at PT Herfinta Farm Plantation. This study used quantitative methods with a descriptive approach. Data were collected through questionnaires distributed to 64 respondents working at PT Herfinta Farm Plantation. Data analysis techniques used were validity and reliability tests, and multiple linear regression analysis. The results showed that leadership had a positive and significant influence on work discipline. Furthermore, rewards also had a positive and significant influence on work discipline. Similarly, supervision had a positive and significant influence on work discipline. Therefore, it can be concluded that effective leadership, reward provision, and appropriate supervision play a role in improving employee work discipline at PT Herfinta Farm Plantation. This study provides important implications for organizations to pay more attention to policies related to leadership, reward systems, and appropriate supervision mechanisms to improve employee work discipline.